2021
DOI: 10.3390/cancers13123032
|View full text |Cite
|
Sign up to set email alerts
|

Cell-Free Total Nucleic Acid-Based Genotyping of Aggressive Lymphoma: Comprehensive Analysis of Gene Fusions and Nucleotide Variants by Next-Generation Sequencing

Abstract: Chromosomal translocations and pathogenic nucleotide variants both gained special clinical importance in lymphoma diagnostics. Non-invasive genotyping from peripheral blood (PB) circulating free nucleic acid has been effectively used to demonstrate cancer-related nucleotide variants, while gene fusions were not covered in the past. Our prospective study aimed to isolate and quantify PB cell-free total nucleic acid (cfTNA) from patients diagnosed with aggressive lymphoma and to compare with tumor-derived RNA (t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 26 publications
0
4
0
1
Order By: Relevance
“…Molecular profiling is also a useful diagnostic tool, particularly when differential diagnosis between SPMTs and metastasis cannot be confirmed by histomorphology. [30][31][32] We found that nine patients had a family cancer history and three showed a third distinct malignant tumor in this cohort. Wang et al recently reported germline variants of DNA repair genes and of genes involved in B cell functions to be potential causes of MPMTs.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Molecular profiling is also a useful diagnostic tool, particularly when differential diagnosis between SPMTs and metastasis cannot be confirmed by histomorphology. [30][31][32] We found that nine patients had a family cancer history and three showed a third distinct malignant tumor in this cohort. Wang et al recently reported germline variants of DNA repair genes and of genes involved in B cell functions to be potential causes of MPMTs.…”
Section: Discussionmentioning
confidence: 61%
“…Multidetector CT, 26 PET/CT, 27 PET/MRI, 28 and endoscopy 29 have been reported to be highly efficient at detecting synchronous tumors. Molecular profiling is also a useful diagnostic tool, particularly when differential diagnosis between SPMTs and metastasis cannot be confirmed by histomorphology 30–32 . We found that nine patients had a family cancer history and three showed a third distinct malignant tumor in this cohort.…”
Section: Discussionmentioning
confidence: 65%
“…The use of peripheral blood LB has been introduced in the early molecular diagnosis of several malignancies, such as lung and colorectal adenocarcinomas, and melanomas, as well [ 19 , 22 , 23 , 24 ]. More recently, LB application to detect aberrant gene fusions has been published for the diagnosis of aggressive lymphoma genotyping [ 25 ]. Little information was found about the utility of LB to identify diagnostic and prognostic biomarkers in BTCs [ 26 ], so for this reason we aimed to quantify and analyze cfDNA management of patients affected by BTC.…”
Section: Discussionmentioning
confidence: 99%
“…Fusions were considered true positive if the fusion event was covered with a minimum of 5 unique reads and the percentage of reads supporting the event was above 10%. 21 , 22 …”
Section: Methodsmentioning
confidence: 99%